Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s12298-009-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Study on the response of diploid, tetraploid and hexaploid species of wheat to the elevated CO2

Abstract: Study was done to compare the response of Triticum aestivum (hexaploid), Triticum durum (tetraploid) and Triticum monococcum (diploid) wheat species to the elevated CO2 using Free Air CO2 Enrichment (FACE) facility. It was demonstrated that the modern cultivar of wheat Triticum aestivum (hexaploid) was largely sink limited. It appeared to have less photosynthesis per unit leaf area than Triticum monococcum (diploid wheat). While leaf size, grain weight and amylase activity increased with the ploidy level from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The changes in lipid composition such as increase in palmate with corresponding decrease in linoliate, have been identified in plants, exposed to elevated CO 2 (Williams et al 1994). Uprety et al (2009) observed significantly greater CO 2 induced increase in mass, length and breadth of grains of hexaploid compared to tetraploid and diploid wheat species in a FACE study (Table 1). They have attributed this variation to the enhanced flow of carbohydrates in hexaploids due to their greater sink capacity.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The changes in lipid composition such as increase in palmate with corresponding decrease in linoliate, have been identified in plants, exposed to elevated CO 2 (Williams et al 1994). Uprety et al (2009) observed significantly greater CO 2 induced increase in mass, length and breadth of grains of hexaploid compared to tetraploid and diploid wheat species in a FACE study (Table 1). They have attributed this variation to the enhanced flow of carbohydrates in hexaploids due to their greater sink capacity.…”
Section: Introductionmentioning
confidence: 91%
“…Model projections also suggest an increase of 1.4 to 4.5°C in earth's temperature by 2100. A significant amount of literature is available on the response of crop plants to elevated CO 2 for their growth, productivity, physiological and biochemical processes and the impact assessment analysis of CO 2 and temperature on these processes in crop plants indicates possibilities of considerable changes in biochemical composition of grains and their nutritional quality (Stafford 2007;Uprety and Reddy 2008;Uprety et al 2009). This review will describe the impact of rising atmospheric CO 2 on the grain characters of wheat, rice, brassica, mungbean and soybean, which are significantly responsive to the elevated CO 2 for their growth and productivity (Kimball 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uprety et al (2009) [15] observed increases in growth and yield with increase in grain starch and decrease in protein concentration in grain as ploidy level increased in Triticum species under mid-FACE system. However there is hardly any information conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The primary effects of rising CO 2 on plants have been well documented and include higher rates of photosynthesis (Garcia et al 1998). Variability in crop responses to the elevated CO 2 (EC) made the agricultural productivity and food security vulnerable to the climate change (Uprety et al 2009). In view of the irreversible rise of atmospheric CO 2 concentration, there is an urgent need for developing crop varieties with the potential of increased utilization of CO 2 to feed the growing population (Kant et al 2012).…”
Section: Introductionmentioning
confidence: 99%